The Impact of Location on Business in Nepal - Rawal, Priyanka (Nepalese Journal of Management, 2025)
This study examines the impact of location on business in Nepal. Business performance is selected as the dependent variable. Similarly, local market condition, target market proximity, accessibility and visibility, socio-cultural factor, competitor proximity and infrastructure and resources are selected as the independent variables. This study is based on primary data with 120 observation. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing business performance in Nepal. The study showed that local market condition has a positive impact on business performance. It means that increase in local market condition leads to increase in business performance. Similarly, target market proximity has a positive impact on business performance. It indicates that increase in proximity to target market leads to increase in business performance. Moreover, accessibility and visibility has a positive impact on business performance. It means that increase in accessibility and visibility leads to increase in business performance. Likewise, socio-cultural factor has a positive impact on business performance. It shows that increase in socio-cultural factor leads to increase in business performance. Similarly, competitor proximity has a positive impact on business performance. It shows that higher the competitors, higher would be the performance in the business. Further, infrastructure and resources has a positive impact on business performance. It shows that higher the infrastructure and resources, higher would be the business performance.